Peran Digitalisasi Dalam Meningkatkan Efektifitas Penjualan Pada Program Jamur Tiram di Baitulmaal Muamalat Jawa Timur - Meidiana (Yayasan Mutiara Hati Moeslem, 2025)
His study examines the role of digitalization in increasing oyster mushroom sales within an economic empowerment program for mustahik initiated by Baitulmaal Muamalat East Java. The main issue addressed is the limited market reach due to conventional promotional methods. The objective is to analyze the effectiveness of digital platforms such as Instagram, Facebook, WhatsApp Business, and culinary community groups in supporting sales. The research uses a qualitative method with a case study approach, involving interviews, observations, and document analysis. The findings show that Facebook culinary groups are the most effective channels for reaching target markets and boosting sales. However, the use of Instagram and personal Facebook accounts remains minima.. In conclusion, digitalization has proven effective in expanding market access and increasing income, though it requires improvements in production capacity and more optimized visual promotion strategies.